The role of computed and magnetic resonance imaging in assessment of the local advancement of malignant tumors of the hearing organ - E. G. Khazarova; E. L. Dronova (Опухоли головы и шеи)
Introduction. Сomputed tomography (СТ) and magnetic resonance imaging (MRI) are the main methods of radiological diagnostics, which makes it possible to objectively assess the local advancement of malignant tumors of the hearing organ and decide on the possibility of surgical intervention.The objective of this scientific research – to determine the main indications for surgical intervention, taking into account the radiological criteria for the lesion of the temporal bone (CT, MRI) in locally advanced outer ear skin cancer. Materials and methods. This research work based on a retrospective and prospective analysis case history for patients with locally advanced external ear skin cancer. These are 45 patients, who received treatment in surgical department of head and neck tumors in N. N. Blokhin National Medical Research Center of Oncology between 1994 and 2020. Patient observation time averaged 30.0 ± 32.3 months (from 0.7 to 117.4 months, median – 12.0 months).Results. The prevalence of the tumor process in cancer of the skin of the external auditory canal in accordance with the staging system for lesions of the temporal bone structures (University of Pittsburgh, 1990), which takes into account CT and MRI signs of damage to the temporal bone and adjacent anatomical structures, is a factor that significantly affects the long-term results of treatment (for disease-free survival: hazard ratio (HR) 4.76, 95 % confidence interval (CI) 1.93–11.73, р = 0.00069; for tumor-specific survival: HR 4.25, 95 % CI 1.74–10.39, р = 0.0015; for overall survival: HR 1.96, 95 % CI 1.07–3.58, р = 0.029).Conclusion. CT and MRI are mandatory methods of radiological diagnosis of patients with skin cancer of the external auditory canal.